The unfortunate case of triple primary malignancies - Mariapan, Kalyani; Lee, Fei Yee; Jasmani, Asraf Haslam; Osman, Mohd Firdauss; Dass, Andre (Universiti Putra Malaysia, 2022)
We herein report a rare case of triple primary malignancies in a single patient. A 51-year-old Burmese lady without a family history of malignancies or known genetic predisposition developed three primary malignancies involving breast, colon and uterus within two years. She was first diagnosed with left metaplastic breast cancer (pT2N0M0) in 2018 and underwent a mastectomy and axillary clearance. She then presented to us with intestinal obstruction and per vaginal bleeding. A CECT abdomen and pelvis was performed and proceeded with emergency right hemicolectomy for obstructed hepatic flexure tumour. The histopathology of the right hemicolectomy specimen revealed mixed neuroendocrine and non-neuroendocrine neoplasm (MiNEN). Endometrial pipelle sampling showed endometroid carcinoma. A multidisciplinary team approach is crucial in managing patients with multiple primary malignancies in order to achieve the best onchological outcomes.